FORMULALARNI HOSIL QILISHNING BA'ZI-BIR USULLARI HAQIDA - Alaminov, M.; Utemuratov, T.; Qıdırnıyazov, A. (SCIENCE and SOCIETY, 2016)
The article deals with some methods of proving the formulas-identities, in particular the method of mathematical induction and the method of unknown coefficients.
Keywords: the method of mathematical induction; the method of unknown coefficients; formula; identity